Supporting patient education using schema theory: A discourse analysis. Issue 5 (October 2018) - Crawford, Tonia; Roger, Peter; Candlin, Sally
Abstract: Background: While patient education has long been an important part of nurses' roles in patient care, research has found difficulties with providing patient education. Sound subject matter knowledge is not enough to give effective and meaningful instruction; pedagogical knowledge is also needed, with an understanding of different aspects of learning processes to inform our teaching methods Despite the importance of patient education, many nurses do not necessarily have pedagogical knowledge regarding how to teach, how to support patient's learning and how to consciously implement strategies into patient education. Aim: By understanding theories that explain how people learn better, and awareness of the consequences of different approaches to giving patient education, nurses can be better informed about how to structure their information-giving in ways that will support patient learning. Methods: Discourse analysis from an interactional sociolinguistic perspective is used to examine authentic nurse-patient health information encounters, mapped against cognitive learning theories, schema theory in particular. Findings: The interactional consequences, when elements drawn from learning theories are implemented, are observable in the data. Discussion: Strategies that support patients' learning include linking information to the patients' prior experience/knowledge, providing information that is relevant to them, and chunking information into unified themes while encouraging patients' active involvement through questioning and clarification of information. Conclusion: Awareness of learning theories and strategies outlined in this paper can strengthen communication skills and assist health professionals to structure patient education in ways that support patients' learning, thereby enhancing patient safety.